PENERAPAN ALGORITMA C4.5 UNTUK DIAGNOSA PENYAKIT DIARE PADA ANAK BALITA BERBASIS MOBILE - Andhika Putra Munggaran; Taufik Hidayatulloh (Swabumi, 2015)
Application of Algorithm C4.5 for Diagnosis of Childhood Diarrhea Based On Mobile. Lack of knowledge of diarrheal disease and limited treatment of diarrheal disease in children under five is often experienced by the elderly. Hence the need for action / early treatment to prevent diarrheal disease toddlers, in this study will be conducted data analysis diarrheal disease in children under five using the classification of the data mining algorithm C4.5 using four parameters: gender, age (months), the frequency of bowel and stool consistency. From 129 the number of cases consisted of 79 cases of patients who contracted diarrhea and 50 cases of patients who were not infected with diarrhea in children under five are obtained from UPTD Puskesmas Cicurug, then obtained 11 rule resulting from a decision tree algorithm C4.5 with not as much class number 7 and number of class rule so much as 4 rule, so it can be concluded that the research that is implemented into this android application can help users,  especially parents in diagnosing diarrheal disease in children under five.